An Error Analysis on the Use of Simple Present Tense in Descriptive Text - Yessy Marzona (Jurnal Ilmiah Pendidikan Scholastic, 2022)
The purpose of this research is to analyze of student’s errors on the use of simple present tense in Descriptive text based on the problem that students felt confused about using present tense in their writing especially Descriptive text. The method of the research is qualitative descriptive. The subject of this research was eleventh grade students of SMA PERTI PPMTI Padang. The result show that the researcher found four types of errors : omission, addition, misformation, misodering. Then, the researcher found the highest error made by students is misformation with 52 % percentages. This problem influenced by student felt confused to understand simple past because they did not know the meaning and differences between regular verb and irregular verb. Therefore, students claimed if they seldom to practice writing paragraph